Enhancing Public Satisfaction Through Optimization of Service Quality, Complaint Handling, and Interpersonal Comunication: A Case Study of Cepogo District Office, Boyolali Regency - Desna Anisah Ratnaningrum; Rini Handayani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of public services, complaint handling, and interpersonal communication on community satisfaction at the Cepogo District Office, Boyolali Regency. Using quantitative methods, this study involves collecting data through questionnaires, observations, and interviews. The results of this study clearly show that the quality of public services, handling complaints, and interpersonal communication have a positive and significant impact on community satisfaction. The quality of public services is the main factor; The better the service provided by the staff, the higher the level of satisfaction felt by the community. In addition, effective complaint handling has proven crucial in increasing satisfaction. Finally, the ability of staff to establish good interpersonal communication with the community contributes significantly to increased overall satisfaction. Quantitatively, the value of the determination coefficient of 69% of the variation in public satisfaction can be explained by the quality of public services, handling of complaints, and interpersonal communication. Meanwhile, the remaining 31% were influenced by other factors outside of this research model.